METODE DEKOMPOSISI DAN METODE BIG-MUNTUK MENYELESAIKAN PROGRAM LINIER VARIABEL FUZZY TRIANGULAR STUDI KASUS: HOME INDUSTRI BOROBUDUR FURNITURE, BOGOR, INDONESIA - Puspitasari, Nanda; Irawanto, bambang; ., Widowati (MATEMATIKA, 2016)
Fuzzy Variable Linear Programming (FVLP) with triangular fuzzy variable is part of not fully fuzzy linear programming with decision variables and the right side is a fuzzy number. SolvingÂ FVLP with triangular fuzzy variables used Decomposition Methods and Big-M Methods by using Robust Ranking to obtain crisp values. DecompositionMethods of resolving cases maximization and minimization FVLP by dividing the problems into three parts CLP. Solving FVLP with Big-M Methods to directly solve the minimization case FVLP do without confirmation first. The optimal solution fuzzy, crisp optimal solution, optimal objective function fuzzy and crisp optimal objective functionÂ generated from Decomposition Methods and Big-M Methods for minimizing case has same solution. Decomposition Methods has a longer process because it divides the problem into three parts CLP and Big-M Methods has a fewer processes but more complicated because the process without divide the problems into three parts